The effect of lifting straps on peak velocity, force, and power - Hori, N.; Appleby, B. B.; Andrews, W. A.; Nosaka, K. (Journal of Australian Strength and Conditioning, 2010)
The clean pull is a common exercise among athletes. Some athletes use lifting straps in this exercise, but efficacy of lifting straps has not been examined. The purpose of the present study was to examine the effects of lifting straps on velocity, force and power during the clean pull. Five male professional Rugby Union players performed two sets of two repetitions of the clean pull with a 140-kg barbell under two conditions: with and without the lifting straps, in a counterbalanced order. An optical encoder was attached to the barbell, and peak velocity of the barbell, and force / power applied to the barbell were obtained through an inverse dynamics approach. The highest value amongst four trials (two sets of two repetitions) in each condition for each subject was used to compare between the two conditions by effect size. Four out of five subjects showed greater peak velocity (10.1-28.5%), force (2.9-34.4%), and power (6.5-46.5%) with the lifting straps, but one subject did not show a difference between conditions. The effect sizes for the velocity, force, and power were 1.22, 1.52, and 1.31, respectively, showing large effects. It is concluded that using lifting straps is beneficial for athletes who wish to enhance velocity, force and power during clean pull.